2005
DOI: 10.1128/jvi.79.5.2780-2787.2005
|View full text |Cite
|
Sign up to set email alerts
|

Vpr Protein of Human Immunodeficiency Virus Type 1 Binds to 14-3-3 Proteins and Facilitates Complex Formation with Cdc25C: Implications for Cell Cycle Arrest

Abstract: Vpr and selected mutants were used in a Saccharomyces cerevisiae two-hybrid screen to identify cellular interactors. We found Vpr interacted with 14-3-3 proteins, a family regulating a multitude of proteins in the cell. Vpr mutant R80A, which is inactive in cell cycle arrest, did not interact with 14-3-3. 14-3-3 proteins regulate the G 2 /M transition by inactivating Cdc25C phosphatase via binding to the phosphorylated serine residue at position 216 of Cdc25C. 14-3-3 overexpression in human cells synergized wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 51 publications
(65 reference statements)
3
60
3
Order By: Relevance
“…The Rad17 and Hus1 proteins involved in the ATR pathway were shown to be required for cell cycle arrest by Vpr (44). Vpr was also shown to bind Cdc25c directly and inhibit Cdc25c phosphatase activity (43,45), perhaps blocking cyclin B1-Cdc2 redundantly with the ATR pathway. Recently Jacotot et al (19) demonstrated that Vpr-(52-96)-induced apoptosis may occur through a direct effect on the mitochondrial permeability transition pore complex and specifically on the mitochondrial adenine nucleotide translocator, a component of the permeability transition pore complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Rad17 and Hus1 proteins involved in the ATR pathway were shown to be required for cell cycle arrest by Vpr (44). Vpr was also shown to bind Cdc25c directly and inhibit Cdc25c phosphatase activity (43,45), perhaps blocking cyclin B1-Cdc2 redundantly with the ATR pathway. Recently Jacotot et al (19) demonstrated that Vpr-(52-96)-induced apoptosis may occur through a direct effect on the mitochondrial permeability transition pore complex and specifically on the mitochondrial adenine nucleotide translocator, a component of the permeability transition pore complex.…”
Section: Discussionmentioning
confidence: 99%
“…In general, this complex is inactivated by Wee1 kinase and activated by Cdc25c phosphatase (41). Vpr mediates cell cycle arrest by phosphorylation and inactivation of Cdc25c phosphatase via activating the ataxia-telangiectasia and Rad3-related (ATR) DNA damage response pathway (42,43). The Rad17 and Hus1 proteins involved in the ATR pathway were shown to be required for cell cycle arrest by Vpr (44).…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, it is possible that the NT-Ago1 protein stabilizes the 14-3-3⅐Cdc25 complex in the cytoplasm independently of the Cdc25 phosphorylation status. Indeed, this is how the Vpr protein of human immunodeficiency virus is thought to delay cell cycle progression at the G 2 /M boundary in mammalian cells by promoting association of 14-3-3 and Cdc25C in a manner that does not require phosphorylation of Cdc25 (35). However, given that we did not observe colocalization between Cdc25-GFP and RFP-NT-Ago1 in the cytoplasm, it seems unlikely that NT-Ago1 functions in a similar manner to Vpr.…”
Section: Discussionmentioning
confidence: 99%
“…The Cdc25 inhibitor rad25 [19], which is a homologue of human 14-3-3 proteins, enhances Vpr-induced G2 arrest when overproduced in fission yeast [39]. Recent studies further show that Vpr binds to Cdc25C and to 14-3-3 in human cells [43][44][45].…”
Section: Cell Cycle G2/m Arrest Induced By Hiv-1 Vprmentioning
confidence: 99%